2016
DOI: 10.18632/oncotarget.9211
|View full text |Cite
|
Sign up to set email alerts
|

JWA loss promotes cell migration and cytoskeletal rearrangement by affecting HER2 expression and identifies a high-risk subgroup of HER2-positive gastric carcinoma patients

Abstract: Background and AimsJWA, a microtubule-associated protein (MAP) involved in apoptosis, has been identified as a suppressor of metastasis, and it affects cell migration in melanoma and its downregulation in tumor is an idependent negative prognostic factor in resectable gastric cancer. HER2 overexpression has been observed in gastric cancer (GC) cells and implicated in the metastatic phenotype. However, the biological role of JWA in migration and its clinical value in HER2-positive GC remain elusive.ResultsJWA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…JWA gene is biologically conserved in evolution and involves several essential functions, including regulations of cell differentiation, DNA repair, cytoskeleton organization, and maintenance of the homeostasis of glucose and lipid metabolism 23 , 32 , 33 . The biological functions of the JWA are achieved largely by regulating the MAPK signaling pathway, which is essential for maintaining basic life activities in organisms 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…JWA gene is biologically conserved in evolution and involves several essential functions, including regulations of cell differentiation, DNA repair, cytoskeleton organization, and maintenance of the homeostasis of glucose and lipid metabolism 23 , 32 , 33 . The biological functions of the JWA are achieved largely by regulating the MAPK signaling pathway, which is essential for maintaining basic life activities in organisms 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with low expression of JWA in tumor tissues usually suffer worse survival than those with high expression 21 , 22 . JWA negatively regulates HER2 expression and inhibits cell proliferation and migration in human gastric cancer cells through transcription and ubiquitination-related mechanisms 23 , 24 . However, it is unclear whether JWA regulates HER2 expression in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have reported that JWA gene is not only conserved in evolution but has several essential functions, including regulations on cell differentiation, DNA repair, cytoskeleton organization, and metabolisms of sugar and lipid [17,28,29]. The biological functions of the JWA gene is achieved largely by regulating the MAPK signaling pathway, which is essential for maintaining basic life activities in organisms [30].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with lower expression of JWA in tumor tissues usually suffer worse survival than those with higher expression [15,16]. JWA negatively regulates HER2 expression and inhibits cell proliferation and migration in human GC cells through transcription and ubiquitination related mechanisms [17,18]. However, the role of JWA in regulating HER2 expression and its underlying mechanism in BC have not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that JWA is a tumor suppressor gene as its downregulation promotes the survival, migration, invasion, metastasis and angiogenesis of a variety of human cancer cells ( 14 , 16 18 , 20 , 21 , 25 27 ). Regarding breast cancers, we have previously shown that JWA enhances As 2 O 3 -induced apoptosis of MCF-7 cells ( 12 , 13 ).…”
Section: Discussionmentioning
confidence: 99%